2013
DOI: 10.1159/000345688
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Related Acute Lung Injury: The Work of DAMPs*

Abstract: Current notions in immunology hold that not only pathogen-mediated tissue injury but any injury activates the innate immune system. In principle, this evolutionarily highly conserved, rapid first-line defense system responds to pathogen-induced injury with the creation of infectious inflammation, and non-pathogen-induced tissue injury with ‘sterile’ tissue inflammation. In this review, evidence has been collected in support of the notion that the transfusion-related acute lung injury induces a ‘sterile’ inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 97 publications
1
54
0
1
Order By: Relevance
“…In the present study, we detected the increased expression level of IFNB1 mRNA in Nutlin-3-treated SMMC-7721 cells, which promotes the anti- [45] . The function of the injury-activated innate immune system is similar to the two sides of a coin [46] . According to the danger hypothesis [47] , over-expressed IFI16 protein released in the extracellular niche acts as a novel alarmin propagating the damaged-signal [32] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we detected the increased expression level of IFNB1 mRNA in Nutlin-3-treated SMMC-7721 cells, which promotes the anti- [45] . The function of the injury-activated innate immune system is similar to the two sides of a coin [46] . According to the danger hypothesis [47] , over-expressed IFI16 protein released in the extracellular niche acts as a novel alarmin propagating the damaged-signal [32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, its etiology is based on the wellknown "two-hit" hypothesis which includes the clinical condition (pre-existing pathology -first hit) of the patient and the transfusion of blood products, especially plasma (second hit). [2,[11][12][13][14] The vast majority of cases mention that the pre-existence of HLA class I, class II and HNA antibodies in the plasma of the donor, react with the neutrophils of the already very sensitive pulmonary mucosa. In a very smaller percentage of cases, it is reported that the pre-existing heavy pathology of the patient could result in a systemic inflammation of lungs which leads to the accumulation of neutrophils in their microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is required for the proof of this hypothesis. [2,12,13,15] In many cases TRALI is confused with other diseases. Therefore, possible causes of acute pulmonary oedema should be excluded, which may be acute haemolytic reaction, pneumonia and cardiogenic pulmonary oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have found that the continuous oxygenation of the acellular perfusate by ventilation of the lung provides ample oxygen delivery to the ex vivo lung with preservation of function over 12 h of EVLP. This avoids the problem of a limited lifespan of red blood cells within the harsh perfusion environment and the resultant production of pro-inflammatory RBC breakdown products [13]. It also significantly simplifies clinical use.…”
Section: Modern Ex Vivo Lung Perfusion Strategiesmentioning
confidence: 99%